(untitled) (Research, Society and Development, 2024)
The study "The Emerging Use of Ozempic® in Obesity Treatment" analyzes the efficacy and safety of semaglutide (Ozempic®), originally approved for type 2 diabetes, in the treatment of obesity. The objective is to review clinical studies to inform clinical practice about the benefits of the medication for weight loss. The methodology includes the review of studies from the SUSTAIN and STEP programs, which investigated semaglutide in different populations, including people with and without type 2 diabetes. The SUSTAIN studies demonstrated significant reductions in blood glucose and HbA1c levels, along with a favorable safety profile. The STEP program showed that semaglutide resulted in an average weight loss between 14.9% and 17.4% after 68 weeks of treatment. The conclusion highlights that semaglutide not only promotes significant weight loss but also improves health parameters such as glycemic control, prevention of cardiovascular events such as stroke and heart attack in people with cardiovascular diseases, and lipid profile, being a promising option in the management of obesity. Medical supervision is essential, given the need for monitoring side effects and dosage adjustments.